ABOUT THE MARGINAL IN STABILITY OF SELFGRAVITATING RING - Abramian, M. G.; Harutyunian, S. V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2000)
The stability of a self-gravitating incompressible ring of large radius (small curvature) at the marginal stability point of an infinite cylinder is investigated. Calculations are performed to a first approximation for a small parameter related to the ring curvature. It is shown that the ring is stable in the region under consideration.